ANALYSIS OF FAMILY SUPPORT FOR MEDICATION COMPLIANCE IN HYPERTENSIVE PATIENTS PARTICIPATING PROLANIS AT PUSKESMAS TEPUS 2 - Maulana Faris Ikhzul Haq; Rachma Greta Perdana Putri; Tira Alfiani Laariya; Leonny Dwi Rizkita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: The Indonesian Ministry of Health has released a list of the most diagnosed non-communicable diseases in 2023, and hypertension, or high blood pressure, was in the first position. One of the risk factors that cause an increase in the incidence of hypertension is patient non-compliance in implementing the therapy program. Family support is one of the factors that has a significant contribution as a patient booster in influencing patient compliance. The family has an important role in the process of supervision, maintenance, and prevention of hypertension complications. Methods: This study is a quantitative study with a cross-sectional approach. Sampling was carried out using the total sampling technique at Tepus 2 Puskesmas. The total is 43 hypertensive patients participating in Prolanis. Data collection was carried out by distributing family support questionnaires and Morisky Medication Compliance Scale (MMAS-8) questionnaires. Bivariate tests were performed using Chi Square and Spearman's rho tests. Results: Univariate results showed that most respondents had sufficient family support, as many as 28 people (65.1%), and a high level of compliance with taking medication, as many as 25 people (58.1%). From the bivariate results obtained, a p-value of 0.001 (p < 0.05) and an r-value of 0.478. Conclusion: There is a relationship between family support and adherence to medication compliance in hypertensive patients participating in Prolanis at Tepus 2 Puskesmas in 2023 with sufficient relationship strength and positive correlation (unidirectional); the better the family support.